2007
DOI: 10.1002/gcc.20441
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation of antigen processing machinery components and association with cervical carcinoma

Abstract: The antigen processing machinery (APM) plays an important role in immune recognition of virally infected and transformed cells. Defective expression of several APM components is associated with progression and clinical outcome in cervical carcinoma. Genetic variation in the genes encoding APM components is known to be associated with risk of occurrence of several malignancies. However, only limited evidence exists supporting the role of single nucleotide polymorphisms (SNPs) in APM components in cervical carci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
87
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(97 citation statements)
references
References 55 publications
8
87
0
2
Order By: Relevance
“…7,10 A study in Netherlands that was similar with our study showed that the decreasing expression of TAP-1 did not having correlation with the survival rate cervical cancer patients. 11 In the study that was conducted to know the expression of TAP-1 and LMP-2 upon mice, found that the tumor incidence was not different from the control group. Even though LMP and TAP was already confirmed to play a role in detecting and presenting antigen towards HLA, but the specific role of each LMP-2, LMP-7, TAP-1 and TAP-2 genes had not been known yet due to inadequate study before.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…7,10 A study in Netherlands that was similar with our study showed that the decreasing expression of TAP-1 did not having correlation with the survival rate cervical cancer patients. 11 In the study that was conducted to know the expression of TAP-1 and LMP-2 upon mice, found that the tumor incidence was not different from the control group. Even though LMP and TAP was already confirmed to play a role in detecting and presenting antigen towards HLA, but the specific role of each LMP-2, LMP-7, TAP-1 and TAP-2 genes had not been known yet due to inadequate study before.…”
Section: Discussionmentioning
confidence: 98%
“…In this study also suggested that LMP-7 and TAP-2 genes polymorphisms was correlated with the progress of the disease. 11 That study was not investigating the correlation with HPV-16 specifically.…”
Section: Discussionmentioning
confidence: 99%
“…Polymorphisms of TAP genes have been associated with various diseases such as tuberculosis (Wang et al, 2012), ankylosing spondylitis (Feng et al, 2009), leprosy (Shinde et al, 2013), idiopathic bronchiectasis (Dogru et al, 2007), cystic fibrosis (Ozbas-Gerceker et al, 2002) and also with the risk of occurence of several malignant tumors including colon cancer (Yang et al, 2005), cervical carcinoma (Mehta et al, 2007) and esophageal carcinoma (Cao et al, 2005). To the best of our knowledge there has been no study on the association of TAP gene polymorphisms with hematological malignancies.…”
Section: Association Of Tap1 and Tap2 Gene Polymorphisms With Hematolmentioning
confidence: 99%
“…TAP gene polymorphisms were found to be associated with colon cancer (Yang et al, 2005), cervical carcinoma (Mehta et al, 2007) and esophageal carcinoma (Cao et al, 2005). However, literature rewieving yielded no specific study on the role of TAP polymorphisms in the pathogenesis of hematological malignancies.…”
mentioning
confidence: 99%
“…Furthermore, in some malignancies the frequency of HLA class I APM downregulation is associated with higher grading, staging, aggressive histology and abnormal DNA content of tumors, which is often more pronounced in metastases when compared to primary lesions and associated with a reduced patients' survival. [52][53][54][55][56][57] Matsushita et al 58 found that a strong HLA-DR-positive expression on colorectal cancer cells was significantly related to better prognosis for the cancer patients. They have also suggested a possible role for c-myc and propose that HLA DR is up-regulated while c-myc is suppressed by interferon gamma (IFN-γ), thus decreasing levels of c-myc in cancer tissue with high levels of IFN-γ.…”
Section: Tumor Escape Hla Expression and The Antigen Processing Machmentioning
confidence: 99%